2014
DOI: 10.2174/1871520614666140418144610
|View full text |Cite
|
Sign up to set email alerts
|

Episensitization: Therapeutic Tumor Resensitization by Epigenetic Agents: A Review and Reassessment

Abstract: Resistance to chemotherapy, biological and targeted therapies is an important clinical problem. Resistance can arise and/or be selected for multiple mechanisms of action. Unfortunately, acquired resistance to antitumor agents or regimens is nearly inevitable in all patients with metastatic disease. Until recently, it was believed that this resistance was unalterable and irreversible, rendering retreatment with the same or similar drugs futile in most cases. However, the introduction of epigenetic therapies, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 42 publications
1
37
0
Order By: Relevance
“…These modified red blood cells act as nanosized anticancer bioagents: their tendency to aggregate is based on an altered deformability as well as the binding of PS, CD36, CD47, CD71, and ICAM-1, the 'Velcro' of the red blood cell membrane, to cognate receptors on the tumor vasculature, which contributes to persistent or recurrent tumor microvascular clogging and stasis [19]. This microvascular occlusion leads to further increase in acidosis and hypoxia, conditions which are required for the hemoglobin-mediated reduction of nitrite to nitric oxide, thereby making RRx-001 a hypoxia-activated anti-cancer agent that induces its own hypoxia [3,21] (Figure 5 (b-d)). …”
Section: Tumor Microvascular Occlusion and Trojan Horselike Rbc Phagomentioning
confidence: 99%
“…These modified red blood cells act as nanosized anticancer bioagents: their tendency to aggregate is based on an altered deformability as well as the binding of PS, CD36, CD47, CD71, and ICAM-1, the 'Velcro' of the red blood cell membrane, to cognate receptors on the tumor vasculature, which contributes to persistent or recurrent tumor microvascular clogging and stasis [19]. This microvascular occlusion leads to further increase in acidosis and hypoxia, conditions which are required for the hemoglobin-mediated reduction of nitrite to nitric oxide, thereby making RRx-001 a hypoxia-activated anti-cancer agent that induces its own hypoxia [3,21] (Figure 5 (b-d)). …”
Section: Tumor Microvascular Occlusion and Trojan Horselike Rbc Phagomentioning
confidence: 99%
“…Importantly, DNMTs have been targeted in therapeutic approaches: specifically, DNMT inhibitors 5-Azacytidine (AZA) and Decitabine are FDA approved for the treatment of hematological malignancies, myelodysplasia, and acute myeloid leukemia 16 .…”
Section: Introductionmentioning
confidence: 99%
“…Preclinical studies of RRx-001 have demonstrated anti-tumor activity in refractory solid tumor models 16, 17 . A phase-1 clinical trial of RRx-001 in advanced solid tumors showed promising anti-tumor activity in a heavily pretreated population, without dose-limiting toxicities 20 .…”
Section: Introductionmentioning
confidence: 99%
“…Its clinic activity against NSCLC is being tested in combination with DNA methyltransferase (DNMT) inhibitor Azacitidine or EGFR inhibitor Erlotinib (Tarceva), but not conventional chemotherapy (http://www.clinicaltrial.gov/ct2/results?term=entinostat&Search=Search). While epigenetic therapy emerges as a new strategy to overcome drug resistance and re-sensitize cancer cells to chemotherapy [22, 23], we wondered whether entinostat might possess such activity as a chemo-sensitizer via inhibition of Survivin. In the current report, we investigated the mechanism of action of entinostat in potentiation of paclitaxel-mediated antitumor activity against NSCLC.…”
Section: Introductionmentioning
confidence: 99%